2014
DOI: 10.1021/tx5002628
|View full text |Cite
|
Sign up to set email alerts
|

Oral or Intraperitoneal Binge Drinking and Oxidative Balance in Adolescent Rats

Abstract: Oxidative imbalance is one of the most important mechanisms of alcohol-induced injury. Acute alcohol exposure induces a significant amount of reactive oxygen species during its hepatic metabolism via the microsomal ethanol oxidizing system. During adolescence, the physiological development is still taking place; therefore, ethanol's effects differ in adolescents compared to that in adults. Because binge drinking is the most important model of ethanol intake used by adolescents and because little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
(73 reference statements)
2
27
0
3
Order By: Relevance
“…Protein oxidation by ethanol has been documented, including in rodents exposed to binge ethanol (Nogales et al, 2014). Like MAO enzymatic activity, protein oxidation was strikingly elevated by binge ethanol exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein oxidation by ethanol has been documented, including in rodents exposed to binge ethanol (Nogales et al, 2014). Like MAO enzymatic activity, protein oxidation was strikingly elevated by binge ethanol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neither binge ethanol nor MAOIs had any significant effect on the protein expression of SOD2 or catalase. Several studies have reported changes in expression/activity of SOD2 and catalase following ethanol exposure, while others have not (Carmiel-Haggai et al, 2003; Artun et al, 2010; Nogales et al, 2014). However, in the brain, catalase is largely responsible for the metabolism of ethanol to acetylaldehyde (Ledesma et al, 2014), which explains why we observed a group effect in binge ethanol-treated rats for increased catalase expression compared to control rats, regardless of MAOI administration.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve-week-old adult male Wistar rats (250–300 g) were purchased from SLC Japan (Shizuoka, Japan) and given a single intraperitoneal injection of 40% ethanol (5 g/kg), which is consistent with animal models of acute (binge) ethanol administration [12,13,54,55,56,57]. A control group was also treated with phosphate buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about adolescent BD and its relationship to hepatic oxidation during this developmental period. In this context, our research group has recently found liver oxidation, an imbalance in hepatic GSH and antioxidant enzymes activities, and an increase in liver NADPH‐oxidase expression in adolescent rats exposed to BD (Nogales et al., ).…”
mentioning
confidence: 98%
“…Previous studies have demonstrated that chronic alcohol consumption partially decreased Se deposits in animals and patients (Park et al., ; Rua et al., ), affecting the expression of selenoproteins (Jotty et al., ) and their antioxidant properties (Ojeda et al., ; Rua et al., ). However, until now—and despite the evidence that BD provokes liver oxidation and affects several antioxidant enzymes’ activities (Nogales et al., )—nothing was known about body Se levels, Se distribution, or selenoprotein expression, especially in the liver, a tissue that is affected by EtOH consumption.…”
mentioning
confidence: 99%